Filtering Sinyal Menggunakan Band Pass Filter - Azhar Al Havis; Liza Fitria (Jurnal SIFO Mikroskil, 2018)
In our daily lives we find many filters, filters from the word itself are filters. Filters vary, there are air filters to filter dirty air to be clean, filters / filters for coffee and tea to filter coffee or tea pulp, and so on. All of them try to filter something to get what we want. The filter here is a frequency filter, from which the filter will filter the frequency. The existing frequency we filter so get the frequency as we want. In this research, signal filtering will be carried out using Band Pass. The band-pass filter will pass signals with frequencies in a certain range and reduce the signal with other frequencies. The sound sample used is the sound of a cat with just one sample. In this sample signal screening is carried out with 5 different frequencies, namely at frequencies of 8000, 16000, 32000, 48000 and 96000. Data retrieval and processing of voice signals are carried out with the help of audacity and Matlab R2010b software. Sound data in the .wav format is filtered to remove noise and filter using a band pass filter. Sounds issued that are received are destructive which eliminate the sound information that is carried. This of course requires that the sound quality received is not good, so it requires sound signal processing to eliminate noise. Then the voice data is processed by voice signal using the FFT (Fast Fourier Transform) method. The results of this study are the output of sound signals that are clean from noise.